Pharmacists-led interventions to improve medication adherence in global health settings - Ranjan Dash, Smruti; Kumar Sahu, Mahendra (Journal of Neonatal Surgery, 2025)
The sword with two sides, Although medicine has the power to cure diseases, it also has the unspoken potential to damage patients if not used properly. Every healthcare system should prioritize ensuring that patients receive the appropriate medication for their clinical condition at the appropriate time, via the appropriate route, and in the appropriate dosages. Polypharmacy can be helpful because various morbidities are so common, but it can also have unintended harmful effects. In order to forecast the course of treatment, the co-morbidity-polypharmacy score correlates the patient's physiological age rather than their chronological age. Any departure from the medication's anticipated positive effect may be seen as a drug-related issue. In this study, the cost-benefit analysis of clinical pharmacy services and the effects of clinical pharmacist interventions on drug-related issues in polypharmacy prescriptions were examined. Finding and addressing drug-related issues, determining the level of health care providers' acceptance of clinical pharmacist interventions, analyzing the cost-benefit of clinical pharmacy services, and creating and recommending a clinical pharmacists intervention form to standardize and record drug-related issues were the specific goals.